Thermal performance of an environmentally friendly nanoliquid in a cabinet with two l-shaped heaters: application for electronic cooling - Ma, Yuan; Mohebbi, Rasul; Yang, Zhigang; Sheremet, Mikhail A. (International journal of numerical methods for heat & fluid flow)
Purpose The purpose of this paper is to analyze numerically the nanofluid natural convection inside a square enclosure with two L-shaped heaters using lattice Boltzmann method. Design/methodology/approach An environmentally friendly nanofluid, clove-treated graphene nanoplatelet (CGNP), is used to study the enhancement of heat transfer. Six various heaters configurations are considered and effects of nanoparticle concentration (0-0.1%) and Rayleigh number (10<^>3-10<^>6) on streamlines, isothermal lines and heat transfer parameters are studied. The developed computational code has been validated using mesh sensitivity analysis and numerical data of other authors. Findings It is observed that in contrast to distilled water, CGNP/water nanofluid is an efficient coolant and the Nusselt number is increased as the nanoparticle concentration and Rayleigh numbers increment. The nanoparticle concentration cannot change the flow pattern inside the enclosure. However, the Rayleigh number and heaters configuration can change the flow pattern significantly. Several heaters configurations (Cases 1-4) related to the symmetry of geometrical shape and corresponding boundary conditions, illustrate the symmetry of streamlines and isotherms about the vertical line (X = 0.5). The formation of vortices inside the enclosure is affected by the raising heat plume above the heaters. Moreover, at different Rayleigh numbers, the relative magnitude of average Nu for various cases is different. At Ra = 103, the energy transport characteristic depends on the relative location of heaters and cold walls, and the order of average Nusselt number is Case 3 similar to Case 4 similar to Case 6 > Case 1 similar to Case 2 similar to Case 5. However, at Ra = 106, an influence of thermal convection mechanism on heat transfer is significant and the ranking of average Nusselt number is Case 1 similar to Case 4 > Case 5 > Case 6 > Case 2 > Case 3. Originality/value The originality of the research lies in both the study of thermogravitational convection in a closed chamber with two L-shaped heaters, and the analysis of the influence of control parameters for an environmentally friendly nanoliquid on electronics cooling process.